2016
DOI: 10.5755/j01.ee.27.2.12288
|View full text |Cite
|
Sign up to set email alerts
|

The role of perceived value and emotions in the satisfaction and future intentions of spectators

Abstract: The quality of service offered by sports entities has become a good predictor of user satisfaction and also future intentions. To know the future intentions of customers of any service is a key objective to develop service improvement and retention strategies. This need has also become apparent to professional sports clubs. In this study, the relationship between perceived quality (tangibles, staff, complementary services and outcome quality), perceived value, emotions, satisfaction and future intentions of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
1
3
1
Order By: Relevance
“…This lack of relationship suggests that the participants in this event give more importance to quality than to the associated costs of attending. The study also does not support the relationship between value and general satisfaction, in contrast to the study of Murray and Howat (2002), Clemes et al (2011), or that of Calabuig-Moreno et al (2016a). The results also give more importance to the emotional aspects related to satisfaction than to value.…”
Section: Discussioncontrasting
confidence: 91%
“…This lack of relationship suggests that the participants in this event give more importance to quality than to the associated costs of attending. The study also does not support the relationship between value and general satisfaction, in contrast to the study of Murray and Howat (2002), Clemes et al (2011), or that of Calabuig-Moreno et al (2016a). The results also give more importance to the emotional aspects related to satisfaction than to value.…”
Section: Discussioncontrasting
confidence: 91%
“…The higher the VAR fan perception value, the higher the actual satisfaction of the fan. Perceived value was identified as the most influential variable in all studies, herein, the results of this study are similar to those of previous ones (Greenwell et al, 2002;Moreno et al, 2015;Calabuig-Moreno et al, 2016). Using the analysis path, it was noted that the fan's perceived value of VAR in enhancing the quality and atmosphere of the game exerted a marginal impact on VAR satisfaction.…”
Section: Discussionsupporting
confidence: 84%
“…In the research on the satisfaction of tennis event spectators, it is observed that the enjoyment and economic perceived value of the spectators exerts a positive impact on satisfaction (Wang et al, 2021). Calabuig- Moreno et al (2016) conducted a study utilized a basketball club in the Spanish League to investigate the satisfaction of 563 spectators to the game, and they noted that the perceived value positively affects the satisfaction of the audience. Similarly, the research on basketball audience satisfaction indicates that perceived value is the most influential factor in sports audience satisfaction (Moreno et al, 2015) and Mostaghimi et al (2016) obtained similar conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Cox and Dale (2001) mentioned that the main distinction between the physical service environment and the website interface is the ability of customization of the services to needs of individuals that companies have. Range of researchers focuses on the evaluation of the quality of website (Davidavičienė, Sabaitytė, and Davidavičius, 2017;Kirk and Abrahams, 2017;Knezevic, Davidaviciene, and Skrobot, 2017;Moreno et al, 2016), and the customer behavior (Claudy, Garcia, and O'Driscoll, 2015;Laudon and Traver, 2016;Saridakis et al, 2015). The peculiarities of navigation and perception of the quality of e-commerce in Lithuania were analyzed by Davidaviciene, Pabedinskaite, and Davidavicius (2017), Davidavičienė, Sabaitytė, and Davidavičius (2017).…”
Section: Delone and Mclean 2004mentioning
confidence: 99%